2022
DOI: 10.3390/ijerph192316215
|View full text |Cite
|
Sign up to set email alerts
|

Nexus of Emotional Intelligence and Learning Outcomes: A Cross-Country Study of China and Pakistan Higher Educational Institutes

Abstract: The purpose of this empirical study is to investigate the effects of emotional intelligence (EI) on learning outcomes (e.g., social, cognitive, and self-growth outcomes) and satisfaction with the university experience of academics and administrative staff at Chinese and Pakistani research universities. This study also investigates the mediation of self-directed learning (personal autonomy, personal responsibility, and personal growth) and knowledge management processes (KMPs) concerning the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…The proposed study can advance our knowledge of how emotional self-awareness and regulation can be promoted in educational settings by looking at the impact of emotional intelligence on teaching methods and student results (Reisenzein 2018). Overall, employing ECT as the theoretical framework for the proposed research can contribute to the provision of a thorough and fact-based understanding of the relationship between teachers' emotional intelligence, and student outcomes (Shafait and Huang 2022) and can offer helpful insights for enhancing educational practices and outcomes.…”
Section: Conceptual Frameworkmentioning
confidence: 95%
“…The proposed study can advance our knowledge of how emotional self-awareness and regulation can be promoted in educational settings by looking at the impact of emotional intelligence on teaching methods and student results (Reisenzein 2018). Overall, employing ECT as the theoretical framework for the proposed research can contribute to the provision of a thorough and fact-based understanding of the relationship between teachers' emotional intelligence, and student outcomes (Shafait and Huang 2022) and can offer helpful insights for enhancing educational practices and outcomes.…”
Section: Conceptual Frameworkmentioning
confidence: 95%
“…Sullivan et al showed, using quantitative testing of physiological indicators, that exposure to green space can help students recover from stress and mental fatigue [5]. Additionally, studies indicate that fostering emotional intelligence has positive effects on university performance [6], enhances teacher creativity [7], and positively influences the learning outcomes of both students and teachers, as well as organizational performance [8,9]. This demonstrates the crucial importance of emotional well-being among knowledge workers for the development of a university.…”
Section: Of 28mentioning
confidence: 99%
“…However, there is a lack of research that explores the inner transformative mechanisms of green space and mental health from a subjective psychological perspective [12,13]. Social ecology emphasizes that the impact of the environment on human health is not independent but is influenced by a number of mediating effects [8]. Some studies explored the intrinsic mechanism between green space and mental health by examining intermediary factors.…”
Section: Of 28mentioning
confidence: 99%
“…Higher education institutions (HEIs) share the same agenda with interactive people directed at adaptation, flexibility, change and success. 1 , 2 In modern psychology, HEIs need emotional intelligence (EI). “EI is the ability to perceive emotions, to access and generate emotions so as to assist thought, to understand emotions and emotional knowledge, and to reflectively regulate emotions so as to promote emotional and intellectual growth”.…”
Section: Introductionmentioning
confidence: 99%